(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2019)
The objective of this paper is to analyze the interaction between the actants (actantial schema) that is the origin of literary work. Our intention is to dissect, according to the narratology, the role assigned to each character by Juan Goytisolo in his novel La resaca. We intend to show that the actants have a certain dynamics, which allows keeping the reader in suspense from the beginning until the end of the work. We have two figurines in the corpus that go through specific process in order to fulfill their assignments.